Computer and Internet Use on Campus: A Legal Guide to Issues of Intellectual Property, Free Speech, and Privacy - S.Hawke Constance (Jossey-Bass, 2000)
A comprehensive, well-written, interesting, and informative guide to technology and Internet use on campus. Everyone—from administrators who oversee and manage computer networks, to faculty interested in distance learning, to student affairs officials trying to understand alleged infractions by students, to college attorneys seeking to understand the law—will find this book enormously helpful. Well chosen vignettes and examples, along with a list of recommendations and guidelines, help make this complicated arena of university life and law accessible to administrators, faculty, and attorneys working in it."—Barbara Lee, dean, School of Management and Labor Relations, Rutgers University